Integrating Strategies of Entrepreneurship- Gourmet Pakistan case study from Pakistan - Zafar, Muhammad Ali (Journal of Medical Biomedical and Applied Sciences, 2014)
This paper aims to get to know how integrating strategies boost up entrepreneurship. The study has shown that the dynamics of prevailing market structure, Applying creativity to develop innovation, culture, entrepreneurial leadership, economic transition, networking structures its stages and management resources are key integrating strategies for entrepreneurship. Moreover, capital and tax polices play a vital role in boosting up entrepreneurship.Study of Gourmet Pakistan gives strong support that mentioned strategies boost up the entrepreneurial process. The researchmethodology used in this paper is face to face interview, financial reports & official website of Gourmet Pakistan.